The effect of various damping on the isolation performance of quasi-zero-stiffness system. (15th May 2022) - Hu, Xiaoying; Zhou, Chunyan
Highlights: This paper discusses the effect of three types of damping (linear viscous damping, linear hysteretic damping, and nonlinear hysteretic damping) on the isolation performance of Quasi-zero-stiffness system in details. Two hybrid-damping models, V-H-NH and N-NH model, based on the real engineering applications of QZS system are proposed and analyzed. The effects of two hybrid-damping models on QZS system are respectively verified by experiments with a hydraulic damper and a TPR damper. Abstract: A quasi-zero-stiffness (QZS) vibration isolation system was designed to attenuate low-frequency and ultra-low-frequency vibrations. Because nonlinearity exists in QZS systems, various nonlinear dynamic behaviours inevitably influence the vibration isolation performance. Thus, damping is the key for suppressing nonlinear effects. The effects of three types of damping, viscous damping, hysteretic damping, and nonlinear hysteretic damping on the QZS vibration isolator are discussed in this paper. The Duffing-Ueda equation was used to describe the dynamic motion of the QZS system, which was solved using the harmonic balance method (HBM). Two hybrid-damping models were then proposed to avoid unbounded nonlinear responses for excessive base excitation. Based on theoretical and numerical analysis, the effect of the two hybrid damping models, the hysteretic-nonlinear hysteretic (H-NH) damping model and viscous-hysteretic-nonlinear hysteretic (V-H-NH) damping model, on the transmissibility is discussed in detail. To verify the theoretical results, QZS isolator prototypes with two types of hybrid damping were designed and manufactured. A hydraulic damper and a thermoplastic rubber (TPR) damper were used respectively in the two models of the experiments. The experimental results reveal that the isolator with hybrid linear and nonlinear damping provides a better isolation effect for both low-and high-frequency vibrations.